(untitled) (Economic and Political Thought, 2017)
There is a common belief that German society and elites’ attitude to Russia differs from the Polish one. It is not the full truth because, as a result of Russia’s policy, the attitude towards Russia has become much more critical in Germany of the 21st century than it was before. However, Germany carries out a more global policy than Poland, thus, because of the importance of Germany and Russia in Poland’s policy, there is an important question what the German vision of Russia’s position in the just developing multipolar world is. The question is even more important as Germany, the strongest state in Europe, stabilising the euro zone, has evident problems with defining its own role on the international arena and overcoming a one-sided geopolitical perception of the world.